Modern Arabic literature - Starkey, Paul, 1947- (New Edinburgh Islamic surveys., 2006)
Provides an introduction to modern Arabic literature of the nineteenth and twentieth centuries. Designed as an introductory textbook for English-speaking undergraduates, this title attempts to situate the development of modern Arabic literature in the context of the medieval Arabic literary tradition.